VD_FINDINFO HC / 2013 / 843 vom 16. Juli 2013 - VD Tribunal cantonal (2013)
RESPONSABILITÉ CONTRACTUELLE, CONTRAT DE TRAVAIL, CONTRAT DE LICENCE, CONTRAT INFORMATIQUE, LOGICIEL | 323b al. 2 CO, 97 al. 1 CO